2003
DOI: 10.1097/01.asn.0000092146.67909.e2
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Functionally Anuric Patients on Automated Peritoneal Dialysis

Abstract: Abstract. The European APD Outcome Study (EAPOS) is a 2-yr, prospective, multicenter study of the feasibility and clinical outcomes of automated peritoneal dialysis (APD) in anuric patients. A total of 177 patients were enrolled with a median age of 54 yr (range, 21 to 91 yr). Previous median total time on dialysis was 38 mo (range, 1.6 to 259 mo), and 36% of patients had previously been on hemodialysis for Ͼ90 d. Diabetes and cardiovascular disease were present in 17% and 46% of patients, respectively. The AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
311
1
12

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(349 citation statements)
references
References 34 publications
(18 reference statements)
25
311
1
12
Order By: Relevance
“…These peritoneal changes, coupled with loss of residual renal function, probably underlie the high prevalence of volume overload seen in many PD patients. Several studies (63)(64)(65) have shown an inverse relationship between daily peritoneal ultrafiltration volume and mortality, data that are consistent with the notion that reduced ultrafiltration capacity and consequent hypervolemia with increasing dialysis vintage may reverse the early survival advantage with PD.…”
Section: Possible Biologic Explanations For Differences In Outcomes Bsupporting
confidence: 58%
“…These peritoneal changes, coupled with loss of residual renal function, probably underlie the high prevalence of volume overload seen in many PD patients. Several studies (63)(64)(65) have shown an inverse relationship between daily peritoneal ultrafiltration volume and mortality, data that are consistent with the notion that reduced ultrafiltration capacity and consequent hypervolemia with increasing dialysis vintage may reverse the early survival advantage with PD.…”
Section: Possible Biologic Explanations For Differences In Outcomes Bsupporting
confidence: 58%
“…Both of these treatment strategies benefit the impaired salt and water removal that is associated with fPTS. The disappearance of increased mortality risk of fPTS in other reported patient cohorts using APD and icodextrin would strongly suggest that fPTS is an intrinsic characteristic of membrane function that can be managed successfully (7)(8)(9). This argues against fPTS as solely a manifestation of systemic inflammation, which would be less responsive to the discussed treatment strategies.…”
Section: Discussionmentioning
confidence: 98%
“…Since 1998, increasing proportions of patients were treated with automated PD (APD), particularly when anuric, as described in the European Automated Peritoneal Dialysis Outcome Study (EAPOS) (9). In patients with solute transport Ͼ0.64 (as assessed by D/Pcr at 4 h) on PET testing), icodextrin was used with increased frequency.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these patients still have an increased risk of mortality. In the European APD Outcomes (EAPOS) study, patients who did not achieve the target UF of 750 ml/d had an increased risk of mortality (P ϭ 0.0047) (50). Therefore, preservation of the PM is essential for improving long-term patient survival.…”
Section: Introductionmentioning
confidence: 99%